The relationship between self-control and online game addiction in adolescents - Felinaweny, Riffa; Kurniawan, Rizal (ARKA INSTITUTE, 2025)
The use of the internet and digital devices has become an important part of teenagers' daily lives, raising concerns about the increasing phenomenon of online gaming addiction. This study aims to examine the relationship between self-control and online gaming addiction among junior high school students in Padang. This study uses a quantitative approach with a correlational design and involves 125 respondents selected through purposive sampling. Data were collected using the Game Addiction Scale (reliability = 0.851) and the Self-Control Scale (reliability = 0.793). Data analysis was performed using Pearson's product-moment correlation technique with the help of the SPSS 20 for Windows program. The results showed a significant positive correlation between self-control and online game addiction (r = 0.483; p < 0.05). These findings indicate that adolescents with high levels of self-control also show a high tendency toward online gaming behavior, meaning that self-control in the context of adolescence does not always function as a protective factor but can be adaptive to social and digital environmental pressures.